Using reflective processes to promote attention To diversity in schools: a study of Practice in chile - López, Ana Luisa (Revista Enfoques Educacionales, 2017)
Over the last decade or so, many writers have argued that inclusive practices are more likely to be developed when school communities are involved in collaborative processes of inquiry, reflection and action in order to learn how to respond to learners’ diversity. The research was carried out in two schools (with names changed for ethical reasons) with different characteristics: Innovacion School, in Santiago, is one of the pioneer schools in the country in integrating disabled students, whilst Loncomahuida School is located in one of the most isolated rural areas of Chile and responds to a high population of students of a Mapuche ethnia.Guided by literature on action research, the study made use of an inclusive action research model that guided the process in both schools. This model emphasises the need to concentrate efforts on the promotion of reflective practitioners, as well as reflective communities. It also involves a team of co-researchers, formed by volunteers from the schools, planned to internalize and coordinate the process in each institution.